Effect of metformin on epicardial adipose tissue in patients with coronary artery disease without diabetes: A cardiac MRI substudy of the MET-remodel trial. (June 2021) - Al-Talabany, Shaween; Mohan, Mohapradeep; Weir-McCall, Jonathan; Gandy, Stephen; Singh, Jagdeep S.S.; Mordi, Ify R.; Baig, Fatima; Maria J Choy, Anna; George, Jacob; Houston, J. Graeme; Struthers, Allan.D.; Khan, Faisel; et al.
Abstract: Epicardial adipose tissue (EAT) is a risk factor implicated in the pathogenesis and prognosis of cardiovascular disease. Metformin has been shown to regress EAT in animal models and observational studies. In this study, we report that metformin has no effect on EAT in patients with coronary artery disease without diabetes. Highlights: Epicardial adipose tissue is associated with the pathogenesis and prognosis of cardiovascular disease. Metformin exhibits cardioprotective effects including anti-inflammatory properties. Metformin treatment has no effect on epicardial adipose tissue compared with placebo in patients with coronary artery disease without type 2 diabetes.